Males and females’ complimenting behaviour on the celebrities’ Instagram comments - Muthiara Chairani; Subiyantoro Subiyantoro (Journal of Applied Linguistics and Literature)
A compliment is a sincerely positive comment, remark, utterance, or expression about the speaker’s intention to have a good relationship with others by delivering positive or good values toward someone else. This research is purposed to analyze complimenting behavior by males and females found on celebrities’ Instagram comments. This research employed descriptive qualitative research through a documentaries method. 250 comments from 10 most-followed celebrities’ (five males and five females) comment columns were used to identify the complimenting behavior in the form of words, phrases, or clauses containing compliments. This revealed that the differences between males and females in complimenting behavior showed who complimented, to whom they complimented, the compliment types, and the compliment forms. Females complimented more than males did. Besides, complimenting celebrities is commonly directed at the same sex rather than across sex. However, both males and females were more likely to use direct compliments and less indirect compliments. Compliments by both males and females also showed that direct compliment form 8 (ADJ NP!) is dominantly used. The dominance of form 8 occurrence indicated that shorter form of compliment seemed suitable and reasonable for a virtual interaction like Instagram. From this research analysis, it can be concluded that some different contexts of communication require other compliment forms. Therefore, adding a sub-category and additional category from the original compliment forms should be considered.